PENGARUH PROFITABILITAS, LIKUIDITAS, UKURAN PERUSAHAAN, RISIKO BISNIS DAN PAJAK TERHADAP STRUKTUR MODAL (Studi pada perusahaan pertambangan yang terdaftar di BEI periode 2014-2017) - Rizki Amalia, 15.05.52.0014; Suwarti, Titiek (Students' Journal of Accounting and Banking, 2019)
This study aims to examine the effect of Profitability, Liquidity, Company Size, Business Risk and Tax on Capital Structure in Mining Sector Companies listed on the Indonesia Stock Exchange for the period 2014-2017. Capital Structure is a balance or comparison between external and internal funds. The sample selection technique used a purposive sample and obtained 16 companies with a period of 4 years so that 64 data were obtained, and processed using the SPSS application. Based on the results of data processing, it was found that Profitability, Business Risk and Taxes did not affect the capital structure. While liquidity has a negative and significant effect on capital structure. Company size variables have a positive and significant effect on capital structure. The results of the test on the coefficient of determination (R2) are 0.459. This means that 45.90% is influenced by profitability, liquidity, company size, business risk and tax while the remaining 54.10% is influenced by other variables.